Spirituality of Service and Silence: Towards a Dialogical Enrichment between Indian and Western Approaches to Authenticity - Kuruvilla PANDIKATTU SJ (Annals of Philosophy, Social and Human Disciplines, 2013)
What are some of the elements of a spirituality relevant for today? How can we formulate a spirituality relevant to the contemporary times? What are some of the orientations of contemporary spiritualities that can make human life more authentic? These are some of the questions we attempt to answer in this article.1 In this quest we are basing ourselves on two broad categories of general spirituality – the Eastern and the Western, though we limit the Eastern understanding primarily to the Hindu and Western primarily to the Christian spiritualities. The aim of this article is to draw some orientations from both these spiritualities which can inspire contemporary search for authenticity. Going beyond the popular stereotypes of the spirituality (and therefore, mysticism) of Indian and Western traditions, this article wants to broadly reflect on the spirituality of the Western tradition as that of service. Then it intends to reflect on the spirituality of the Indian tradition as that of silence. This is followed by giving two illustrations of two great spiritual personalities which may be complemented by “Spirituality of Silence,” of the Eastern tradition. Examples are given of two cotemporary seers to illustrate these tendencies. Finally, we advocate a spirituality that is open to the world and that enters into creative dialogue with other traditions.